PENDUGAAN JENIS KELAMIN MENGGUNAKAN CIRI-CIRI MORFOLOGI DAN PERILAKU HARIAN PADA GELATIK JAWA (Padda oryzivora Linn, 1758) DI PENANGKARAN - Muhammad Rekapermana; Machmud Thohari; Burhanuddin Masyud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
Java sparrow is endemic species to Java, Bali and Bawean Island, but now introduced widely to Southeast Asia region and Srilangka. The species now scarce as a result of massive capture for the pet trade. A research on sex determination using morphological characteristics and daily behaviour of Java sparrow was carried out on May-July 2005 at Bogor. 12 unsexed individuals of Java sparrow were used in this observation. The birds put in two separate cages. The research resulted that sexing error of the sample sparrows using morphological characteristics was only 16.7%. Daily activity pattern of male and female birds was not much difference, but the male tends to be more active than female. Among its behaviour, twitter was the only characteristic which distinguish sex of the sparrows.Keywords : Sex determination, Javan sparrow, morphology, behaviour, captive breeding